Hepatic Regeneration: If it Ain’t Broke, Don’t Fix it - GY Minuk (Canadian Journal of Gastroenterology)
The capacity for the liver to regenerate after injury or resection has long been recognized, as implied by the legend of Prometheus. Resections of up to 70% of the liver are followed by a sequence of events that generally result in complete restitution of hepatic mass and function. Hypertrophy of hepatocytes begins within hours, with accumulation of amino acids and triglycerides and activation of enzymes that are associated with proliferative activity. Increased DNA synthesis is associated initially with hyperplasia of hepatocytes, and then other cells, which begins in the periportal region and spreads in a wave-like fashion to the pericentral region of the lobule. Quiescent hepatocytes are primed to enter the cell cycle and then proceed through the G1/S and G2/M restriction points, under the influence of a variety of proteins, growth factors (especially hepatocyte growth factor) and cycle dependent kinases. At each stage there is interplay between growth promoters and inhibitors, including transforming growth factor-beta and GABA. Factors that initiate hepatic regeneration are unknown, and might include hepatic depolarization, increases in blood flow, destruction of liver matrix (with release of growth factors), and increased production or expression of growth promoters compared to inhibitors. Regenerative activity increases with the amount of resection to a point, and then relatively declines. Uncontrolled proliferation of liver tissue after resection or injury is not necessarily beneficial, because it could lead to a diversion of resources from the maintenance of hepatic function and to an increased risk of neoplasia. Therefore, it is unclear whether clinicians should attempt to enhance hepatocyte regeneration. Since both hepatic regeneration and metabolic function require energy from high-energy nucleotide triphosphates, especially adenosine triphosphate (ATP), a reasonable strategy might be to augment energy delivery and ATP production. Mortality rates after limited (fewer than 70%) resections and mild or moderate injuries of previously normal livers are low, and supportive care is often sufficient. The prognosis is unclear; however, in cases of more massive resection, resections in the setting of underlying liver disease or cirrhosis, and fulminant hepatic failure, and liver transplantation is still an important option.